Pemeliharaan Allah Di Masa Pandemi COVID-19: Sebuah Refleksi Teologis Berdasarkan Kitab Ester - Robi Prianto; Yohanes Hasiholan Tampubolon (Manna Rafflesia, 2022)
The Covid-19 pandemic has resulted in the presence of various theological reflections. One of the topics discussed was about God's providence. This paper will present a theological reflection based on the book of Esther on God's providence. This study uses a qualitative approach with a descriptive exegesis approach by focusing on the structure of the book of Esther. This study found that although there is no name "God" in the book of Esther, God still shows His providence. The absence of the name Allah shows that human actions are not in a different domain. God chose Esther, a woman who came from an “ordinary” background. So that during the pandemic, we are required to actively participate in caring for others as a form of God's care.